The measurement of public goods: Lessons from 10 years of Atkinson in the United Kingdom - Fred Foxton; Joseph Grice; Richard Heys; James Lewis (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2019)
When considering issues of measuring welfare beyond gross domestic product (GDP), a key ongoing, but unfinished, agenda concerns how to measure the outputs of goods and services which are "free at the point of delivery". Public services such as schools and health services are major examples of this kind. Over a decade ago, Sir Tony Atkinson provided a principled framework for this end. Consistent with the basic principles of national accounting, he advocated an approach by which this output should be measured as the value added by the services concerned, where this equates to the incremental contribution to (monetised consumer utility from) outcomes resulting from the delivered outputs. This value, in turn, equated to the improvement in outcomes directly attributable to the activities of the public services concerned. Implementing this approach, as Atkinson recognised, is by no means straightforward, but the United Kingdom experience shows that considerable improvements can be made. Working with experts and practitioners, quantity and quality measures can be identified and used to give a good approximation of the value added by key public services, and thus their contribution to GDP. New data and intelligent use of existing data means this can be done at low cost and in a way which maximises stakeholder understanding and acceptance. But national statistical institutes are also now grappling with a second task; measuring changes in welfare or well-being more generally, regardless of how they are generated. Health outcomes - for example, life expectancy or healthy life expectancy - are influenced by a variety of factors besides publicly-funded health services: diet, smoking prevalence and other lifestyle choices are obvious determinants. So, the central tasks under this agenda become firstly the identification of appropriate measures of outcome changes, secondly determining how much value our societies place on those changes, and thirdly to understand the relationship between the impact of the public service and other factors on the headline outcome measures.
Keywords: C46; C82; E01; H4; H5; I1; I21; I38; K42; 047; 330; national accounts; GDP; public sector; services; economic well-being; quality adjustment; productivity